Hubungan Ambang Rasa Asin dengan Kejadian Hipertensi pada Remaja di Surabaya: Hubungan Ambang Rasa Asin dengan Kejadian Hipertensi pada Remaja di Surabaya - Qayra Syifadhiya; Farapti Farapti (Amerta Nutrition, 2023)
Background: Hypertension is a condition where arterial blood pressure is constantly high and influenced by various factors. High blood pressure in adolescent years increases the risk of hypertension in adulthood. The taste sensitivity which affects the food intake can be observed by conducting the salty taste threshold test. Objectives: This study was conducted to observed the association between the salty taste threshold and the incidence of hypertension in adolescents in Surabaya. Methods: This study used a cross-sectional design and simple random sampling technique for subjects. Primary data were collected through a questionnaire for subject characteristics and salty taste threshold using 3-AFC method with 5 different sodium concentration. The association between the salt taste threshold and hypertension was tested using correlation spearmann. Results: The results of this study were 4.2% of male respondents had both high salty taste threshold and were classified as hypertension. The results of the association test between high salty taste threshold and hypertension in adolescent boys showed a p-value of 0.027 (r=0.320) for systolic blood pressure and a p-value of 0.003 (r=0.422) for diastolic blood pressure. Conclusions: There is significant association between the salty taste threshold and hypertension.